Urinary podocalyxin as an early biomarker for diabetic nephropathy - Md. Sabbir Hossain; Shamsia Tasnim Dwipi; Nazma Ahmed; Khaled Mahbub Murshed; Kazi Ali Aftab; Abdullah Al Mahdi; Md. Mojibul Hoque; Md. Jobayer Hossain Taraq; Md. Zakir Hussain; Md. Abul Kalam Azad (PLoS ONE, 2026)
Background Conventional biomarkers, such as the urinary albumin-to-creatinine ratio (uACR), detect diabetic nephropathy (DN) late in its course and may miss early podocyte injury. Urinary podocalyxin (u-PDX), a sialylated glycoprotein shed from podocytes, may offer an earlier means of detection. Methods We conducted a cross-sectional analytical study at Bangabandhu Sheikh Mujib Medical University between March 2023 and August 2024. Eighty-eight adults were enrolled: 59 participants with type 2 diabetes mellitus (T2DM) and 29 healthy controls. Participants with diabetes were stratified into normoalbuminuric (n = 29), microalbuminuric (n = 15), and macroalbuminuric (n = 15) subgroups based on uACR. Clinical variables and biochemical indices were recorded. u-PDX concentrations were measured using ELISA, and associations with uACR and eGFR were analyzed using Kendall’s tau-b and Pearson’s correlation coefficients. Diagnostic performance was assessed using receiver operating characteristic (ROC) curves with bootstrap internal validation. Results Among participants with diabetes, u-PDX levels increased progressively across normo-, micro-, and macroalbuminuric groups (p < 0.001). u-PDX correlated positively with fasting blood glucose, post-glucose plasma glucose, HbA1c, serum creatinine, serum urea, and uACR, with the strongest correlation for uACR (r = 0.79, p < 0.001), and inversely with serum albumin (r = −0.62, p < 0.001) and eGFR (r = −0.51, p < 0.001). In pairwise ROC analysis, a u-PDX cutoff of 0.80 ng/mL discriminated healthy controls from diabetic patients without albuminuria (sensitivity 100.0%, specificity 96.4%); 1.60 ng/mL discriminated diabetic patients without albuminuria from those with microalbuminuria (86.7%, 93.1%); and 5.51 ng/mL discriminated microalbuminuric from macroalbuminuric patients (86.7%, 93.3%). For overall discrimination of albuminuria-defined DN among diabetic patients, the optimal u-PDX cutoff was 2.92 ng/mL (AUC 0.96, 95% CI 0.90–1.00). Conclusions Urinary podocalyxin is a sensitive early biomarker of diabetic nephropathy, rising before overt albuminuria and correlating with albuminuria severity and declining eGFR. However, longitudinal validation is required before u-PDX can be recommended for routine screening in adults with T2DM.